Do public sector organizations ensure labor ethics? Perspectives from ethics and workplace spirituality in Bangladesh's garment sector. (4th December 2019) - Uddin, Mohammad Jasim; Hossain, Farhad; Fujimoto, Yuka; Ahmed, Jashim Uddin
Summary: The suppression of labor rights is a matter of serious concern in developing countries. Yet little is known about the role of public agencies in protecting the rights of underprivileged employees. Hence, this study aims to examine the reasons behind the persisting labor exploitation in private enterprises despite the presence of public governance and labor codes. Data was collected through in‐depth interviews as well as archives from different external and internal agencies of privately owned garment enterprises in Bangladesh including public administrators and multinational retailers. Kantian ethics and Islamic moral principles were used as theoretical lens to evaluate the labor practices of enterprises. This study contributes to the existing literature by introducing a process model of labor exploitation that depicts multinational power and poor governance to be the main drivers for the abuse of labor ethics. Specifically, political influence and institutional corruption drive poor governance. Public power is exercised to suppress marginalized labor institutions rather than enact labor codes. We found that ethical and spiritual values are not reflected in labor practices and practical suggestions on enacting labor ethics through which the fair enforcement of public power is offered.